Penerapan Administrasi Bisnis Berbasis Komputer pada Penjualan Beras pada Kantor Bulog - Wahyuni, Elmania; Shelly, Djo (Insan Kreasi Media, 2024)
This article discusses the implementation of Community Service Program (KKN) at BULOG Regional Office of West Nusa Tenggara (NTB). This KKN program aims to provide practical experience to students in applying the knowledge they have learned in college to the real world of work, especially in the field of food logistics. KKN activities cover various aspects such as logistics management, data processing, administration, and development of work programs that support the efficiency and effectiveness of BULOG operations. The methods used include orientation and introduction to the agency, implementation, and evaluation. The results of this activity indicate that students can make real contributions to improving the quality of services and operations of the BULOG Regional Office of NTB, as well as gain insights and practical skills that are useful for their future careers. The main purpose of this article is to educate the academic and practical community to generate new ideas for the development of several dynamic complexes.